Crescendo, diminuendo and subito of the trumpets: winds of change in the concerted evolution between flowers and pollinators in Salpichroa (Solanaceae) - Ibañez A.C. (2019)
‘Gradual’ vs ‘punctuated’ and ‘unidirectional’ (only lengthening) vs. ‘bidirectional’ (lengthenings and shortenings) modes of evolution are explanations that compete to explain adaptive changes of flower tube length in angiosperm. The nightshade genus Salpichroa Miers, with 21 species mostly growing in the tropical Andes of southern South America, has the opportune qualities of including nearly 15-fold inter-specific variation in corolla tube length, as well as one species that is a candidate for participating in evolutionary escalation with the longest-billed hummingbird, Ensifera ensifera. We reconstructed the phylogenetic relationships using five molecular markers, the two plastid markers trnD-trnT and trnL, and three nuclear markers, ITS and two COSII, and estimated divergence times of the genus in order to reconstruct the history of both corolla tube length and pollination mode (i.e. hummingbirds, moths or multiple). We used comparative methods to determine whether corolla tube elongation/shortening is associated with shifts in pollination mode and to test, modes and rates of corolla tube change. We found evidence of both lengthening and shortening of corolla tubes. Evolutionary rates are consistent with rapid corolla tube length transitions that are only partly associated with shifts in pollination mode. Though ‘punctuated’ evolution (i.e. large changes predominantly at speciation events) explained corolla changes in the whole genus, ‘gradual’ evolution (i.e. gradual changes during a coevolutionary race with the same pollinator) was a better explanation for the change in the long-flowered clade, mostly pollinated by hummingbirds.